Refuse/Refuge: Castaways on Islands of Exception. Issue 1 (2nd January 2023) - Prentice, Chris
Abstract : At various points in their (post)colonial histories, the border-protective politics of Australia and Aotearoa New Zealand have mobilized off-shore islands as spaces of "inclusive exclusion". Yet, even as spaces of exception and/or exclusion, off-shore islands dismantle inside/outside distinctions. I discuss a selection of Australian and Aotearoa New Zealand novels featuring both literal and metaphorical islands used for removal, internment or containment of Indigenous peoples and wartime "enemy aliens". Through their attention to the poetics of island form, and coasts as more-than-human spaces, the novels underscore how islands bring the relation between inside and outside into question, complicating the articulation of borders .